2011
DOI: 10.1029/2011ja016654
|View full text |Cite
|
Sign up to set email alerts
|

Structure, force balance, and evolution of incompressible cross-tail current sheet thinning

Abstract: [1] THEMIS five-point observations on April 8, 2009 were used to study thinning of the current sheet in the near-Earth tail that led to the onset of a small substorm. Taking advantage of a fortuitous alignment of the five spacecraft near 2300 LT and 11 R E and within 1.5 R E of the current sheet center, latitudinal gradients are analyzed. A significant latitudinal pressure gradient is present indicating the necessity of a (J × B) z force to maintain the pre-onset equilibrium state. During thinning the total pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
5
16
1
Order By: Relevance
“…Our work has demonstrated for the first time that as a macroscopic coherent process, the ideal MHD ballooning instability is capable of inducing the formation of plasmoids in the magnetotail configuration without relying on any microscopic, kinetic, or turbulent processes. In light of recent evidence found in ground and in situ observations for the presence of ballooning instability in the pre‐onset auroral and plasma sheet structures [ Saito et al , , ; Panov et al , ; Motoba et al , , ], our findings on the ballooning instability‐induced plasmoid formation may indeed provide a solid and practical scheme for ballooning instability in the near‐Earth magnetotail to play a critical role in triggering the substorm onset process.…”
Section: Summary and Discussionsupporting
confidence: 62%
“…Our work has demonstrated for the first time that as a macroscopic coherent process, the ideal MHD ballooning instability is capable of inducing the formation of plasmoids in the magnetotail configuration without relying on any microscopic, kinetic, or turbulent processes. In light of recent evidence found in ground and in situ observations for the presence of ballooning instability in the pre‐onset auroral and plasma sheet structures [ Saito et al , , ; Panov et al , ; Motoba et al , , ], our findings on the ballooning instability‐induced plasmoid formation may indeed provide a solid and practical scheme for ballooning instability in the near‐Earth magnetotail to play a critical role in triggering the substorm onset process.…”
Section: Summary and Discussionsupporting
confidence: 62%
“…The data gaps in Ey GSM are caused by this processing. For the calculation of the plasma pressure, ion density, ion velocity and ion temperature, we use the method discussed in the Appendix A of Saito et al [2011].…”
Section: Magnetotail Evolution During This Substormmentioning
confidence: 99%
“…Both patterns of B L behavior have been found in THEMIS and Cluster data. Using a case study Saito et al [] suggested that the j y increase may not necessarily be accompanied by growth of the lobe magnetic field B L , and thus, CS thinning can be (at least at sometimes) driven by internal magnetotail processes rather than by the solar wind. From statistics of Cluster observations of significant j y growth, Thompson et al [] and Snekvik et al [] showed that j y and B L both increase during CS thinning.…”
Section: Introductionmentioning
confidence: 99%